Institutional violence and quality of service in obstetrics are associated with postpartum depression - Souza, Karina Junqueira de (2017)
Objective: to investigate the association between institutional violence in obstetrics and postpartum depression (PP depression) and the potential effect of race, age, and educational level in this outcome. Methods: this is a cross-sectional study about the health care conditions for the maternal and child population of the Federal District, Brazil, carried out in 2011. The study has used a probabilistic sample of 432 women, whose children were aged up to three months, stratified by clusters. Indicators of institutional violence and demographic characteristics have been used in a logistic regression model to estimate the probability of occurrence of postpartum depression. Results: the model has identified a high prevalence of postpartum depression, being it higher among non-white women and adolescent females, besides having a strong positive association between the several indicators of obstetric violence and postpartum depression. Positive interactions on a multiplicative scale have also been observed between: violence by negligence by health care professionals and race and age; physical violence from health care professionals and age; and, verbal violence from health care professionals and race. Conclusions: the indicators adopted to reflect institutional violence in obstetric care are positively associated with postpartum depression, which calls for a reflection on the need to make the health care protocols adequate to the precepts of the Brazilian humanization of childbirth care policies and changes in the obstetric care model.